A Determination of the Concentration Level of Lead 210 PB Isotope in Solid Samples for the Assessment of Radiation Risk Occuring in Coal Mines - Michał Bonczyk (Journal of Sustainable Mining, 2013)
Lead 210Pb, an element of the natural uranium radioactive decay series, is not currently considered a source of radiation risk, especially in a radiation protection system in underground mines in Poland. However, it could be a completely independent element of the radioactive series due to its physical and chemical properties. Routine measurements showed significantly higher than expected concentrations of 210Pb in underground radium rich sediments, based only on the radioactive decay law. This phenomenon implies a need of 210Pb concentration monitoring in such sediments. Nevertheless, the laboratory analysis of 210Pb by gamma radiation spectroscopy is connected with a particular hindrance, the self-attenuation of 210Pb radiation in samples. Current work describes a practical method for obtaining the self-attenuation correction factor in the case of 210Pb concentration analysis. Experimentally obtained correction factors range between 0.51–6.96 cm2/g. Neglecting this factor can cause a significant error or underestimations in radiological risk assessment.